Heavy metal content of herbal health supplement products in Dubai - UAE: a cross-sectional study - Naseem Mohammed Abdulla; Balazs Adam; Iain Blair; Abderrahim Oulhaj (BMC, 2019)
Abstract Background Lead, mercury, cadmium, chromium, and arsenic intoxication have been associated with the use of health supplement (HS) products. The aim of this study is to estimate the concentration of heavy metals in HS products that are on sale in Dubai, United Arab Emirates, premises and to compare estimated daily metal intake with regulatory standards. Methods Dubai-area premises selling HS products were identified by searching the Dubai Municipality database to identify all pharmacies, para-pharmacies and nutrition and healthcare shops. A total of 859 premises were identified in the Deira and Bur-Dubai areas. Data collection was performed between September 1 and December 12, 2016. During that period, all premises that had been identified within Dubai were visited and samples for laboratory testing were collected. Results A total of 200 HS products were tested for lead, mercury, cadmium, chromium and arsenic. High proportion of samples were found to contain metals less than the limits of the detection (LOD) of the method. It was found that 93% of products contained Arsenic (As) < LOD, 94.5% of lead (Pb) < LOD, 100% of Cadmium (Cd) < LOD, 99% of Mercury (Hg) < LOD and 23.5% of Chromium (Cr) < LOD. Using the single imputation method to account for LOD, estimates for the average daily intake of lead was 0.88 μg compared to the tolerable daily intake (TDI) of 20 μg, daily intake of mercury was 0.09 μg (TDI = 20 μg), daily intake of cadmium was 0.83 μg (TDI = 6 μg) while for arsenic it was 0.92 μg compared to the tolerable daily intake of 10 μg. The average daily intake of chromium was 7.57 μg with no internationally established TDI. Assuming users followed the manufacturers' instructions, daily intake of arsenic, lead and mercury would not exceed TDI for any of the 200 products. However, the daily intake of cadmium exceeded or approximated the TDI for three products. Conclusions In this study we found low levels of metals in the products that were available for sale in Dubai. With few exceptions, if the products were used according to the suppliers' instructions, average daily intake of heavy metals will be well below the recommended tolerable daily intakes.